2017
DOI: 10.18849/ve.v2i1.58
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizures Versus Syncope: Pathophysiology and Clinical Approach

Abstract: Generalised epileptic seizures and syncope are two syndromes with similar clinical manifestation and their differentiation can be quite challenging. The aim of this review is to use an evidence-based approach in differentiating these two syndromes through the comprehension of the pathophysiological mechanisms involved and their clinical signs. Both syndromes affect regions of the forebrain and consciousness level, although, different mechanisms are involved. Syncope is a paroxysmal event secondary to a short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Therefore, although clinical symptoms and signs can help the physician to make a rapid diagnosis, it is difficult to distinguish between the two conditions based only on clinical manifestations. 15 In a study of children with unexplained syncope by Alehan et al, 25 the sensitivity and specificity of the HUTT with pharmacological simulation were 76.6% and 86.7%, respectively. Many studies have demonstrated the diagnostic effectiveness of the HUTT in children and adolescents in vasovagal syncope.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, although clinical symptoms and signs can help the physician to make a rapid diagnosis, it is difficult to distinguish between the two conditions based only on clinical manifestations. 15 In a study of children with unexplained syncope by Alehan et al, 25 the sensitivity and specificity of the HUTT with pharmacological simulation were 76.6% and 86.7%, respectively. Many studies have demonstrated the diagnostic effectiveness of the HUTT in children and adolescents in vasovagal syncope.…”
Section: Discussionmentioning
confidence: 96%
“…Cardiac channelopathies often manifest with convulsive syncope, leading to a misdiagnosis of epilepsy which puts these patients at risk of developing serious and life-threatening arrhythmias [40]. Differentiation of generalised epileptic seizures and syncope can also be quite challenging in veterinary medicine, since the two syndromes can share a similar clinical manifestation [41,42]. None of the dogs in this study had an arrythmia misdiagnosed as MRE as a cause for pseudoresistance.…”
Section: Discussionmentioning
confidence: 81%
“…Ein kritisches Überdenken der Differenzialdiagnosen ist an dieser Stelle essenziell. Insbesondere Synkopen sind je nach Ausprägung u. U. schwierig von epileptischen Anfällen zu differenzieren 39 . Dasselbe kann auch auf episodisch auftretende Bewegungsstörungen – sogenannte paroxysmale Dyskinesien – zutreffen.…”
Section: Vorgehen Bei Inadäquater Reduktion Der Anfallsfrequenzunclassified